Interlanguage Errors In Oral Narrative Made By Students Of Man I Boyolali - Suhartini, Suhartini; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Anam Sutopo, M.Hum (2014)
The objective of this research are to describe the pronounciation errors, speech errors, lexical errors and grammatical errors,each types of errors, also find out the dominant and frequency each type of errors that occurance in oral narrative made by students of MAN I Boyolali. In this research, the writer uses a qualitative method. The object of this research is the second grade students of MAN I Boyolali. The subject are 55 students. The sources of the data are informant and documents. The collected errors are identified and classified using Chomsky and Hale theory, Clark and Clark theory, Selinker theory, Krasen and Burt and Linguist Category Taxonomy as a guideline. To describe the errors the writer uses Surface Strategy Taxonomy. The findings present the types of pronounciation errors, speech errors, lexical errors and grammatical errors, their detailed description, and frequency of occurence of types of errors. It is wished that this study may give a new perspective in advanced learners'pronounciation errors, speech errors, lexical errors and grammatical errors. The result of this research shows that there are twenty four types of errors: 228 vowel errors or 41,30℅, 61 to be present or 11,05℅, 47 verb in past tense or 8,51℅, 29 repeats or 5,25℅, 27 bound morpheme 'ed' or 4,89℅, 25 silent pause or 4,53℅, 19 consonant error or 3,44℅, 18 correction or 3,26℅, 17 plural marker {-s} or 3,08℅, 15 stutter or 2,72℅ , 15 adjective form or 2,72℅ , 14 lexical words or 2,36℅, 7 addition to or1,27℅,6 filled pause or 1,09℅, 6 modal auxiliary in negative form or 1,09℅, 3 auxiliary verb 'did'or 0,54℅, 3 addition 'ed'or 0,54℅, 3 article or 0,54℅, 2 interjection or 0,36℅, 1 slip of tongue or 0,18℅. The dominant errors is vowel errors is 228 or 41,30℅